Variabilidad en caracteres morfologicos relacionados con la implantacion de Desmanthus virgatus (L.) Willd. y Desmanthus paspalaceus (Lindm.) Burkart - Zabala, J.M.=700 1 Giavedoni, J.; Tomas, P.A.; Budini, E.A.
(Es, En)
Ilus. 30 ref
Keywords: LEGUMINOSAS FORRAJERAS; DESMANTHUS VIRGATUS; ESTABLECIMIENTO DE PLANTAS; ARGENTINA; AGRISCENTIA